2007
DOI: 10.1136/gut.2006.110858
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a second-generation  2  ligand (pregabalin) on visceral sensation in hypersensitive patients with irritable bowel syndrome

Abstract: Pregabalin increased distension sensory thresholds to normal levels in IBS patients with rectal hypersensitivity. A concomitant increase in rectal compliance appeared to be unrelated to the reduction in sensitivity. These data suggest that alpha(2)delta ligands are worthy of further investigation in the treatment of visceral pain disorders, including IBS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
132
0
4

Year Published

2008
2008
2016
2016

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 179 publications
(143 citation statements)
references
References 30 publications
7
132
0
4
Order By: Relevance
“…9,[15][16][17][18][19] The barostat was programmed to deliver a series of phasic isobaric rectal distensions 60 s in duration, separated by 60 s periods, during which bag pressure returned to the IOP. Distension stimuli were programmed to increase by 4 mmHg with each distension until the subject reported pain.…”
Section: Distension Protocolmentioning
confidence: 99%
“…9,[15][16][17][18][19] The barostat was programmed to deliver a series of phasic isobaric rectal distensions 60 s in duration, separated by 60 s periods, during which bag pressure returned to the IOP. Distension stimuli were programmed to increase by 4 mmHg with each distension until the subject reported pain.…”
Section: Distension Protocolmentioning
confidence: 99%
“…19 Viscerosomatic responses can also be evoked by colorectal distension, but we chose a writhing test since colonic distension has a lower degree of inflammation and is more conducive for specific abdominal pain associated with altered colonic sensitivity such as in irritable bowel syndrome. 10,11,23,28 Availability and ease of management were the main reasons for using mice instead of rats 7,14-18 and intraperitoneal injection instead of other routes of administration. The duration of the test was set at 30 min to reduce variability and obtain a rapid result.…”
Section: Resultsmentioning
confidence: 99%
“…A clinical trial with irritable bowel syndrome patients suffering from rectal hypersensitivity showed that pregabalin increased the distension sensory thresholds to normal levels Houghton et al [30] . This is supported by the recent work of Meymandi and Keyhanfar [2] who stated that pregabalin had five times the potency of gabapentin and 1/85 th the potency of morphine in animal models of visceral pain.…”
Section: Discussionmentioning
confidence: 99%